You are currently browsing the tag archive for the ‘Laplaciano 3d’ tag.

Laplaciano en cartesianas:

\Delta u = \Sigma_i \frac{\partial^2}{\partial x_i^2}u

1d

\frac{u_{i-1}-2u_i+u_{i+1}}{h^2} = f_i

\frac{1}{h^2}u_{i-1} + \frac{1}{h^2}u_{i+1} +\frac{-2}{h^2}u_i= f_i

2d

\frac{u_{i-1,j}-2u_{i,j}+u_{i+1,j}}{h_x^2} + \frac{u_{i,j-1}-2u_{i,j}+u_{i,j+1}}{h_y^2} = f_{i,j}

i fijo:

\frac{1}{h_y^2}u_{i,j-1} + \frac{1}{h_y^2}u_{i,j+1} +(\frac{-2}{h_x^2}+\frac{-2}{h_y^2})u_{i,j}= g_{i,j}(:=f_{i,j} + \frac{-1}{h_x^2}u_{i-1,j} + \frac{-1}{h_x^2}u_{i+1,j})

j fijo:

\frac{1}{h_x^2}u_{i-1,j} + \frac{1}{h_x^2}u_{i+1,j} +(\frac{-2}{h_x^2}+\frac{-2}{h_y^2})u_{i,j}= g_{i,j}(:=f_{i,j} + \frac{-1}{h_y^2}u_{i,j-1} + \frac{-1}{h_y^2}u_{i,j+1})

3d

\frac{u_{i-1,j,k}-2u_{i,j,k}+u_{i+1,j,k}}{h_x^2} + \frac{u_{i,j-1,k}-2u_{i,j,k}+u_{i,j+1,k}}{h_y^2} + \frac{u_{i,j,k-1}-2u_{i,j,k}+u_{i,j,k+1}}{h_z^2} = f_{i,j,k}

i,j fijos:

\frac{1}{h_z^2}u_{i,j,k-1} + \frac{1}{h_z^2}u_{i,j,k+1} +(\frac{-2}{h_x^2}+\frac{-2}{h_y^2}+\frac{-2}{h_z^2})u_{i,j,k}= g_{i,j,k}

(g_{i,j,k}:=f_{i,j,k} + \frac{-1}{h_x^2}u_{i-1,j,k} + \frac{-1}{h_x^2}u_{i+1,j,k} + \frac{-1}{h_y^2}u_{i,j-1,k} + \frac{-1}{h_y^2}u_{i,j+1,k})

i,k fijos:

\frac{1}{h_y^2}u_{i,j-1,k} + \frac{1}{h_y^2}u_{i,j+1,k} +(\frac{-2}{h_x^2}+\frac{-2}{h_y^2}+\frac{-2}{h_z^2})u_{i,j,k}= g_{i,j,k}

(g_{i,j,k}:=f_{i,j,k} + \frac{-1}{h_x^2}u_{i-1,j,k} + \frac{-1}{h_x^2}u_{i+1,j,k} + \frac{-1}{h_z^2}u_{i,j,k-1} + \frac{-1}{h_z^2}u_{i,j,k+1})

j,k fijos:

\frac{1}{h_x^2}u_{i-1,j,k} + \frac{1}{h_x^2}u_{i+1,j,k} +(\frac{-2}{h_x^2}+\frac{-2}{h_y^2}+\frac{-2}{h_z^2})u_{i,j,k}= g_{i,j,k}

(g_{i,j,k}:=f_{i,j,k} + \frac{-1}{h_y^2}u_{i,j-1,k} + \frac{-1}{h_y^2}u_{i,j+1,k} + \frac{-1}{h_z^2}u_{i,j,k-1} + \frac{-1}{h_z^2}u_{i,j,k+1})

Anuncios
noviembre 2017
L M X J V S D
« Ago    
 12345
6789101112
13141516171819
20212223242526
27282930